2016
DOI: 10.1176/appi.ps.201400581
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating Behavioral Health Disparities and Improving Outcomes for Racial and Ethnic Minority Populations

Abstract: Integrated care holds promise for reducing mental health disparities for racial and ethnic minority groups, but studies are lacking. The authors consider critical components of effective integrated models for minority populations, including cultural and linguistic competence and a diverse workforce, and describe emerging best practices. To successfully implement integrated models into practice with minority populations will require guidance from communities, consumers and family members, and national experts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 10 publications
0
47
0
Order By: Relevance
“…42,[55][56][57] A 2016 literature review concluded that "Evidence is lacking about the effectiveness of integrated care offered in a culturally and linguistically competent, patient-centered framework that adequately addresses key concerns and barriers that affect populations at great risk for marginal health." 58 To address this evidence gap, Project THRIVE (Towards Health Recovery and Vital Engagement) offers a promising approach. Project THRIVE is a health disparity research project designed to develop, implement, and evaluate a culturally centered model of integrated care in a predominantly African American population.…”
Section: Integrated Care Models In Culturally Diverse Populationsmentioning
confidence: 99%
“…42,[55][56][57] A 2016 literature review concluded that "Evidence is lacking about the effectiveness of integrated care offered in a culturally and linguistically competent, patient-centered framework that adequately addresses key concerns and barriers that affect populations at great risk for marginal health." 58 To address this evidence gap, Project THRIVE (Towards Health Recovery and Vital Engagement) offers a promising approach. Project THRIVE is a health disparity research project designed to develop, implement, and evaluate a culturally centered model of integrated care in a predominantly African American population.…”
Section: Integrated Care Models In Culturally Diverse Populationsmentioning
confidence: 99%
“…It is important to examine the IBHC model with diverse and underserved samples (Sanchez, Chapa, Ybarra, & Martinez, 2012). For instance, although Hispanic patients generally receive less quality mental health care (Young, Klap, Sher-bourne, & Wells, 2001), seek services less often (U.S.…”
Section: The Current Study: Three Questions and An Extensionmentioning
confidence: 99%
“…In light of recent research which suggests Blacks may be at particular risk for poor treatment outcomes, largely due to early drop out, novel strategies to increase patient engagement are necessary (Saloner & Le Cook, 2013). Such strategies may help reduce barriers to treatment, which include socioeconomic stressors, a general mistrust of medical providers and mistreatment based on race (Sanchez, Ybarra, Chapa, & Martinez, 2016). Findings of lower probability of use in the exercise group were similar for Whites, though not significant.…”
Section: Discussionmentioning
confidence: 99%